(-4又2/3)+(-3又1/3)+6又1/2+(-2又1/4) 计算
1个回答
-4又2/3+(-3又1/3)
6又1/2+(-2又1/4)
=-8+6又2/4+(-2又1/4)
=-8+4又1/4
=-3又3/4
相关问题
(-4又1/3)-(+3又1/3)-(6又1/2)+(-2又1/4)计算
一道计算题(过程)急!-2又1/3+1又1/6+4又1/4-1又2/3-(-2.75)
计算(+6又3/5)+(-5又2/3)+(+4又2/5)+(+2又1/7)+(-1)+(-1又1/7)
计算算式(两题,(-3又1/2)-(-2又1/3)-(-1又1/2)-(-5又3/4) {计算,(-1又1/3)+|(-
计算:-(-3又1/2)-(+5/6)-(-2又3/4)
(1)-(1又 1/2)+(-5/6)+(2又 3/4)-(-3/8)-(+4 又2/3)
计算 6.75-2又2/9+3又1/4-3又7/9=?2又1/3-3/5×1.25=?1又8/15÷【3-【3/4+1/
1.2又3/4-(-1又1/2)-3又1/4+(-4又1/2)+4= 2.|5又1/11-3又4/17|+4又4/17-
2又4/5*[1/(3又1/3-2.4)] 计算
几道数学计算题1.(--3又5/6)+(2又2/5)-(+2又1/6-(-7又3/5)2.(-0.6)-(-3又1/4)